Desain Poster Edukatif Sebagai Strategi Penguatan Program PKK Berbasis Masyarakat Di Desa Panggung Baru - Afian Syafaadi Rizki; Mamed Manalu; Khairul Anwar Hafizd; Nindy Permatasari; Sausan Hidayah Nova (Cattleya Darmaya Fortuna, 2026)
The Family Welfare Movement (PKK) plays a vital role in community development at the village level. However, the effectiveness of its programs often faces challenges due to suboptimal communication strategies and a lack of engaging information media for the residents of Panggung Baru Village. Information regarding health, parenting, and domestic economy is frequently delivered through conventional methods that fail to capture public interest or ensure long-term retention. This community service project (PKM) aims to design and implement a series of educational posters as a visual communication strategy to strengthen community-based PKK programs. The goal is to transform complex program guidelines into easily digestible, visually appealing, and culturally relevant information. The project employs a participatory design approach consisting of four main stages: Situation Analysis: Identifying the specific needs and information gaps within the Panggung Baru community,Creative Design: Developing poster content using persuasive language and modern graphic design principles tailored to the local demographic,Implementation: Distributing and displaying posters in strategic public areas and PKK meeting points,Measuring the increase in community awareness and engagement through qualitative interviews and observation. The implementation of these educational posters is expected to significantly enhance the visibility of PKK initiatives. By utilizing visual media, the program aims to foster better understanding of family welfare concepts, encourage proactive community participation, and provide a sustainable educational tool that persists beyond formal meeting hours. Ultimately, this strategy serves as a scalable model for other villages looking to modernize their community empowerment programs through creative media.